The influence of high-intensity work on the record power profile of under-23, pro team, and World Tour cyclists - Leo, P.; Mateo-March, M.; Giorgi, A.; Muriel, X.; Javaloyes, A.; Barranco-Gil, D.; Pallarés, J. G.; Lucia, A.; Mujika, I.; Valenzuela, P. L. (International Journal of Sports Physiology and Performance, 2024)
Background Durability (ie, the ability to attenuate the decline in performance after accumulated work) has been identified as a performance determinant in elite cyclists. The aim of the present study was to compare durability in elite cyclists of various performance levels, particularly after high-intensity work, referred to as "high-intensity durability."